Agonistic politics in post‐crisis landscapes: Comparative insights from Athens and Madrid. Issue 3 (13th January 2022) - Arampatzi, Athina; Janoschka, Michael
Abstract: Critical debates in human geography have interrogated the changing political landscapes of the post‐2008 crisis period and the post‐democratic imprint of neoliberal reconfigurations in Europe. Moreover, geographers have offered insights into politicisation processes that disrupted the post‐crisis consensus, attesting to the possibility inherent within forms of democratic politics. Contributing to these debates, this paper critically engages with Chantal Mouffes "agonistics" approach, aiming to deliberate on the implicit geographies of her thought and bring forward the complex, messy, and multi‐scalar geographies of democratic politics. In so doing, the paper offers an empirically informed comparative perspective of two exemplary cases of governance changes. Social solidarity economy (SSE) and housing inform our re‐conceptualisation of "agonistics, " through a plural reading of the co‐existing and at times conflicting forms of political agency and democratic politics of this period. By conceptualising the multiple and heterogeneous spatialities, modalities, and temporalities of agonistics in Athens and Madrid, we acknowledge their mutual constitution and distinct analytical validity for geographical thinking. Comparing across uneven geographical contexts elicits crucial tensions emanating from the heterogeneity of the two contexts and further allows us to distillate the diverse, yet complementary, logics and analytical dimensions of agonistics. Eventually, our contribution aims to problematise the distinction between "politics" and "the political" – as either neatly spatialised around pre‐given state spaces or understood exclusively as disruptive moments and ruptural events – and draw the attention to actually existing forms of agonistic politics. Abstract : The paper critically engages with Chantal Mouffe's "agonistics" approach, aiming to deliberate on the implicit geographies of her thought and bring forward the complex, messy, and multi‐scalar geographies of democratic politics. In so doing, it offers an empirically informed comparative perspective of two exemplary cases of governance changes in Athens and Madrid, which inform our re‐conceptualisation of "agonistics", through a plural reading of the spatialities, modalities, and temporalities of democratic politics.